Pemetaan Aksesibilitas Jalan di Nagari Lawang Berbasis Sistem Informasi Geografis - Yanti, Delvi; Yusman, Rival Doli; Irsyad, Fadli; Stiyanto, Eri; Puari, Aninda Tifani Puari (Warta Pengabdian Andalas, 2025)
Road infrastructure is a crucial element in supporting socio-economic growth, particularly in rural areas such as Nagari Lawang, Agam Regency, West Sumatra. This article discusses efforts to map road conditions in Nagari Lawang using Geographic Information Systems (GIS). The objective of this mapping is to enhance road accessibility, which can support the economic growth of the local community, especially in the agriculture and tourism sectors. The methodology includes road accessibility surveys and data analysis using ArcGIS software. Survey results indicate that the roads in Nagari Lawang are predominantly concrete with an average width of 2 meters, while dirt roads are narrower and mainly used as farm roads. The resulting map is expected to assist the government in more targeted and equitable development planning. This road mapping not only supports infrastructure development but also aligns with the Merdeka Belajar Kampus Merdeka (MBKM) program as a collaborative effort in regional development to the head of the Lawang village government.